Distribute and add like terms and you are good
alirghty
we can make it easier by simplifying what we can
(4v-6v)=-2v so
(-2v)-1(v-5v³)+(5v³+3)=
-2v-v+5v³+5v³+3=
10v³-3v+3
Answer:
32
Step-by-step explanation:
lets substitute the appropriate values in the equation:
5h+3 - j h= 6 j=1 , so we have:
5*6 +3 -1
30 +3 -1
32
Answer:
Step-by-step explanation:
2y = 3 -2x
Rearrange the equation to slope-intercept form
y = -x + 3/2
Slope of line is 3/2.
Answer:
Step-by-step explanation:
0
r
= 1
2x-x=-13+5
x=-8
I think so
Good luck